2000
DOI: 10.1016/s0896-6273(00)00015-5
|View full text |Cite
|
Sign up to set email alerts
|

Tetanic Stimulation Recruits Vesicles from Reserve Pool via a cAMP-Mediated Process in Drosophila Synapses

Abstract: At Drosophila neuromuscular junctions, there are two synaptic vesicle pools, namely the exo/endo cycling pool (ECP) and the reserve pool (RP). We studied the recruitment process from RP using a fluorescent dye, FMI-43. During high-frequency nerve stimulation, vesicles in RP were recruited for release, and endocytosed vesicles were incorporated into both pools, whereas with low-frequency stimulation, vesicles were incorporated into and released from ECP. Release of vesicles from RP was detected electrophysiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
145
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(162 citation statements)
references
References 27 publications
16
145
1
Order By: Relevance
“…Some work has suggested that cAMP signaling increases the size of the recycling vesicle pool at already active synapses (Kuromi and Kidokoro, 2000;Menegon et al, 2006). With neither brief 30 min FSK stimulation nor our standard 4 h FSK stimulation paradigm did we observe reliable increases in the intensity of FM1-43FX labeling of synapses that might have indicated an increase in the recycling vesicle pool.…”
Section: Camp and Presynaptic Potentiationcontrasting
confidence: 59%
“…Some work has suggested that cAMP signaling increases the size of the recycling vesicle pool at already active synapses (Kuromi and Kidokoro, 2000;Menegon et al, 2006). With neither brief 30 min FSK stimulation nor our standard 4 h FSK stimulation paradigm did we observe reliable increases in the intensity of FM1-43FX labeling of synapses that might have indicated an increase in the recycling vesicle pool.…”
Section: Camp and Presynaptic Potentiationcontrasting
confidence: 59%
“…Short-term potentiation of Ca 2ϩ -regulated exocytosis by PKA has been reported previously in several types of secretory cells such as chromaffin cells, pancreatic ␤ cells, and neurons (O'Sullivan and Jamieson, 1992;Morgan et al, 1993;Ä mmälä et al, 1994;Trudeau et al, 1996;Kuromi and Kidokoro, 2000). In addition to these types of cells, it has been recently shown that PKA also potentiates Ca 2ϩ -regulated exocytosis of endosomes with lysosomal markers in normal rat kidney fibroblasts (Rodríguez et al, 1999).…”
Section: Early Potentiation Of Exocytosis and Facilitation Of Membranmentioning
confidence: 71%
“…Elucidating whether cAMP signaling is involved is confounded by the facts that wholesale manipulations of cAMP levels through cAMP analogs and AC activation potently and bidirectionally affect release probability and result in diverse neurophysiological outputs at MFTs (48,49). Nevertheless, it is wellestablished that manipulating cAMP levels at various types of presynaptic terminals alters the dynamics of STP (50)(51)(52)(53). Of particular interest is that chronically elevated cAMP levels can affect synaptic facilitation through effects on vesicular pools (54), and animals lacking AC8, which acts as a presynaptic calcium sensor, have WM but not long-term memory deficits (55), similar to Disc1 Tm1Kara animals.…”
Section: Discussionmentioning
confidence: 99%